ANALISIS YURIDIS PENERAPAN HUKUM TERHADAP TINDAK PIDANA PERDAGANGAN ORANG YANG MENYEDIAKAN JASA SEKS KOMERSIAL (Studi Putusan Nomor 484/Pid.Sus/2018/PN.Sby) - Ensklopedi Sarumaha (Jurnal Panah Hukum, 2022)
Commercial Sex Service Provider is a business actor who provides or provides services by offering himself as a sexual gratification to others by expecting payment, in the form of money, for the services he has performed. One of the crimes of providing commercial sex services that have been examined and tried by the Surabaya District Court is decision number 484/Pid.Sus/2018/PN.Sby. On July 5, 2018, the perpetrator was sentenced to 1 (one) year in prison for violating Article 506 of the Criminal Code regarding the act of pimping (suonteneur), meaning the act of providing commercial sex services. The type of research used is normative legal research with an approach, legislation approach, case approach, and analytical approach. Data was collected using secondary data, which was obtained through library materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis used was descriptive qualitative data analysis and the conclusion was drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the application of the law to the criminal act of trafficking in persons who provide commercial sex (study of decision number 484/Pid.Sus/2018/PN.Sby) is in the analysis of the judge's decision based on the decision of the Surabaya district court, stating that the perpetrator Ahmad Jawari bin Mardiono has been legally and convincingly proven guilty of committing the crime of